Error Analysis for Localizing Egocentric Multimodal Cues in the Presence of Helicopter Noise. (September 2015) - Brill, J. Christopher; Rupert, Angus H.; Lawson, Ben D.
Loss of situation awareness (SA) remains a problem in aviation and can result in spatial disorientation (SD). Attempts to remedy the problem through non-visual displays have used 3-dimensional (3D) audio and vibrotaction. It is possible that the operational environment may not facilitate the use of 3D audio aircraft noise, fore-aft sound confusions, and pilot hearing loss. The present study looked at the effect of the first variable (ambient noise) on participants' performance for localizing egocentric 3D audio, tactile, and redundant audiotactile cues in the presence of continuous helicopter noise. Accuracy rates were significantly better and errors were less disperse for tactile and audiotactile cues, suggesting that displaying information to pilots through these modalities could yield substantially better performance versus 3D audio alone.